التحليل الوظيفي للجملة العربية - الوظائف التركيبية أنموذجا Functional Analysis Of The Arabic Sentence - Structural Functions As A Model - مرباح, شفاعة; عبيزة, عايشة (جامعة الوادي - University of Eloued, 2022)
بعدما ظهرت اللسانيات الغربية واتّسعت رقعتها، تزايد الاهتمام بعلوم اللسان في العالم العربي كثيرا، حيث أسهم كثير من العلماء الذي احتكّوا بالدراسات الغربية في التعريف باللسانيات، ورصد أثرها على القضايا العربية، وكان أحد هؤلاء أحمد المتوكل، بتأليفه مجموعة من الكتب قدم من خلالها مشروعا يسعى به إلى إعادة قراءة التراث اللغوي وفق الامتدادات الحديثة، فرصد ظواهر العربية وحاول تفسيرها بالانطلاق من المنهج الوظيفي . وارتأينا أن نركز في هذه الدراسة على الدراسة الوظيفية للجملة العربية ،على اعتبار الجملة العربية هي الوحدة الأساسية التي يتشكل منها الكلام، والنواة الأولى للنصوص، وذلك بالنظر لوظائفها التركيبية، ثم تحديد الدور الأساسي لتلك الوظائف التي تسهم في إبراز الخصائص النحوية الوظيفية للجملة العربية . ومن هنا فالإشكالية المطروحة تتمثل في: ما هي أهم الوظائف التركيبية التي درسها المتوكل وخصائصها؟و كيف نستثمر هذه الوظائف في النحو العربي ؟ للإجابة على الإشكالية المطرحة اتبعنا المنهج الوظيفي لنبرز من خلاله الخصائص الوظيفية للوظائف التركيبية في الجملة العربية. . After Western linguistics appeared and expanded, interest in linguistics increased a lot in the Arab world, as many scholars who came into contact with Western studies contributed to the definition of linguistics,and monitoring its impact on Arab issues, and one of these was Ahmed Al-Mutawakil, He authored a number of books through which he presented a project ,that seeks to ré-read the linguistic heritage according to modern extensions. He traced the phenomena of Arabic and tried to explain them based on the functional approach. Considering the Arabic sentence is the basic unit of speech, And the first nucleus of the texts, we decided to focus on the functional study of the Arabic sentence in view of its structural functions, and then define the basic role of the structural functions that help highlight the functional characteristics. Hence, Hence, the problem posed is: What are the most important structural functions that Al-Mutawakil studied and their characteristics? And how do we invest these functions in Arabic grammar? To answer the problem posed, we followed the functional approach to highlight the functional characteristics of the structural functions in the Arabic sentence.
مقال
Keywords: التحليل الوظيفي ; الوظائف التركيبية ; الفاعل ; المفعول ; النحو الوظيفي; Functional analysis ; structural functions ; subject ; object ; functional grammar